Frugal Living in Islamic Finance: How QRIS Supports Ethical Spending? - Refky Fielnanda; Pujiono Pujiono; Iwan Hermawan; Irma Novida; Istiyanti Istiyanti; Eri Nofriza (Universitas Nurul Jadid, 2025)
Frugal living, or a frugal lifestyle, embodies a concept that coincides with Islamic financial principles, emphasising equilibrium, sustainability, and the avoidance of excessive consumerism. The concept of frugal living has gained increasing relevance in modern economic discourse, particularly in response to financial instability, environmental concerns, and the need for responsible resource management. In the digital age, the payment system utilising the Quick Response Code Indonesian Standard (QRIS) has gained prominence as a tool for facilitating more efficient and transparent financial transactions. This study examines how the use of QRIS within the Islamic financial framework can enhance ethical consumption practices aligned with the tenets of frugal living. This research, employing a qualitative methodology through literature analysis, determined that QRIS effectively diminishes cash utilisation, which may foster impulsive spending, enhances precise financial documentation, and reinforces Sharia financial principles such as justice, transparency, and sustainability. This approach promotes more inclusive and efficient transactions, aligning with the maqashid shariah objectives of preserving individual and societal welfare. This research suggests that the digitalisation of Islamic finance via QRIS can serve as a strategic tool for fostering more ethical and responsible consumer practices.